EU structural funds and regional income convergence: A sobering experience - Philipp Breidenbach; Timo Mitze; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
The European Structural and Investment Funds (ESIF) are the prime instrument of EU regional policy. European policy makers place considerable hope into their growth stimulating funding measures to overcome current economic stagnation. Consequently, there is a strong need for credible evidence regarding the programs' effectiveness. Based on an empirical identification strategy linked to modern growth theory, we find that the disbursement of EU structural funds is negatively correlated with regional growth. Incorporating spatial dynamics and decomposing this correlation into a direct and a spatially-indirect component, it is particularly the latter which determines this 'sobering' finding. Regarding the economics behind these results, the obtained negative spatial effect may reflect the role played by policy-induced spatial competition among neighboring regions. It could also highlight the backwardness in technological endowment and economic structures of highly funded regions. In any case, EU structural funding does not seem to contribute effectively to foster income convergence across regions. – – Die europäischen Struktur und Investmentfonds (ESIF) sind das wichtigste Instrument der EU-Regionalpolitik; die europäische Politik setzt große Hoffnungen in die wachstumsstimulierende Wirkung dieser Fördermaßnahmen zur Überwindung der aktuellen wirtschaftlichen Stagnation. Basierend auf einer empirischen Identifikationsstrategie können in diesem Papier keine Belege für positive Förderwirkungen gefunden werden. Werden räumliche Strukturen berücksichtigt, zeigt sich, dass räumlich indirekte Effekte dieses Ergebnis beeinflussen - also solche Regionen weniger wachsen, deren Nachbarn stark gefördert werden. Neben der potenziellen Erklärung, dass Nachbarn gegenseitig ihre Investoren abwerben, legt dieses Resultat nahe, dass hochgeförderte regionale Cluster unter struktureller und technologischer Rückständigkeit leiden, die durch Wachstumsprogramme nicht überwunden werden. Beide möglichen Erklärungen lassen den Schluss zu, dass die Förderung ihr eigentliches Ziel, die Konvergenz der Regionen, verfehlt.
Keywords: C21; R12; R58; 330; EU regional policy; Solow growth model; spatial spillovers; panel data